A plea to redirect and evaluate the success of South American's Podocnemidid river turtle (2015)
ABSTRACT: We review the current practices of podocnemidid turtle conservation programs in South America and summarize the direct and indirect negative consequences that some of these practices may have on the populations we are attempting to manage. We argue that programs that only focus on nest transfer and head-starting as their conservation strategies would be better served by redirecting their efforts toward the protection of subadults and adults and in conducting monitoring programs designed to evaluate the impact of their management practices. Also, we make suggestions for other ways that the management of podocnemidid populations may be improved without resorting to manipulative ex situ practices that may well do more harm than good.